Bile Formation and Secretion. Issue 3 (July 2013) - Boyer, James L.
Abstract: Bile is a unique and vital aqueous secretion of the liver that is formed by the hepatocyte and modified down stream by absorptive and secretory properties of the bile duct epithelium. Approximately 5% of bile consists of organic and inorganic solutes of considerable complexity. The bile‐secretory unit consists of a canalicular network which is formed by the apical membrane of adjacent hepatocytes and sealed by tight junctions. The bile canaliculi (∼1 μm in diameter) conduct the flow of bile countercurrent to the direction of portal blood flow and connect with the canal of Hering and bile ducts which progressively increase in diameter and complexity prior to the entry of bile into the gallbladder, common bile duct, and intestine. Canalicular bile secretion is determined by both bile salt‐dependent and independent transport systems which are localized at the apical membrane of the hepatocyte and largely consist of a series of adenosine triphosphate‐binding cassette transport proteins that function as export pumps for bile salts and other organic solutes. These transporters create osmotic gradients within the bile canalicular lumen that provide the driving force for movement of fluid into the lumen via aquaporins. Species vary with respect to the relative amounts of bile salt‐dependent and independent canalicular flow and cholangiocyte secretion which is highly regulated by hormones, second messengers, and signal transduction pathways. Most determinants of bile secretion are now characterized at the molecular level in animal models and in man. Genetic mutations serve to illuminate many of their functions. © 2013 American Physiological Society. Compr Physiol 3:1035‐1078, 2013.